Acquisitions of non-controlling equity stakes: Agency conflicts and profitability. (May 2022) - Pinelli, Michele; Cappa, Francesco; Peruffo, Enzo; Oriani, Raffaele
While past research on minority acquisitions has ignored how agency conflicts could prevent acquirers from realizing value creation opportunities, this study investigates whether principal–agent and principal–principal conflicts with the target's managers and controlling shareholder hinder acquirers' ability to capture value from acquisitions of non-controlling equity stakes. Using archival data from a global sample of 443 minority acquisitions announced between 2011 and 2019, we found that cumulative abnormal returns are positively associated to minority shareholder protection and negatively associated to the presence of a strong controlling shareholder in the target firm. We also found that acquisitions of small non-controlling equity stakes amplify the negative effect of the strong controlling shareholder, which instead weakens if acquirers purchase large non-controlling equity stakes. This study contributes to the development of our understanding of the conditions that expose acquirers to value losses from minority acquisitions by examining the intricate bundle of agency conflicts with the target's managers and controlling shareholder. In so doing, this study also provides useful insights to business practice.